Dukungan Suami Terhadap Pemberian Asi Eksklusif Pada Ibu Menyusui - Boediarsih Boediarsih; Berty Widya Astuti; Indah Wulaningsih (JENDELA NURSING JOURNAL, 2021)
Background: Breast milk is a liquid formed from a mixture of two substances, namely fat and water contained in a solution of protein, lactose and inorganic salts produced by the mother's breast glands and is useful as baby food and breastfeeding for six months without drinking or drinking. any food, including clear water, vitamins and medicine without the addition of any fluids. A good and correct feeding pattern for babies is to exclusively breastfeed babies from birth to 6 months of age and continue until the baby is 24 months old. Husband's support is a vital part in the success or failure of breastfeeding.Research Objectives: to find out the relationship between husband's support for exclusive breastfeeding for breastfeeding mothers in Batursari Village, Batangan District, Pati Regency.Methods: The type of research used is quantitative with a cross sectional approach. The population studied were breastfeeding mothers in Batursari Village, Batangan District, Pati Regency as many as 40 breastfeeding mothers. Chi-square was used to analize the data.Results: breastfeeding mothers in Batursari Village, Batangan District, Pati Regency, mostly had good husband support as many as 24 respondents (66.7%) and gave exclusive breastfeeding as many as 21 respondents (58.3%). There is a relationship between husband's support for exclusive breastfeeding for breastfeeding mothers in Batursari Village, Batangan District, Pati Regency.Conclusion: Husband’s support is very important to help mother sucseed in breastfeeding.